Plan de marketing para el mejoramiento de las ventas en la Empresa Industria Madera Viscarra de la ciudad de Guaranda, provincia Bolívar, período 2023-2027 - Llanos Averos, Yessica Patricia (2024)
The main purpose of this research is the creation of a Marketing Plan aimed at strengthening the sales volume of the company Industria Madera Viscarra, located in Guaranda. The study is based on a representative set of 382 individuals, whose analysis revealed a remarkable recognition of the company by the respondents, supported by its long trajectory in the local market. In addition, it was identified the significant relevance given to special offers and the possibility of implementing a direct delivery service to the client. These strategies are seen as effective means of increasing the loyalty of current customers and attracting new buyers. Ultimately, the importance and necessity of executing specific actions such as launching special offers, establishing a direct-to-customer delivery service and strengthening an active presence on social media platforms is emphasized. These components are considered fundamental for the successful fulfillment of the objectives outlined in the Marketing Plan conceived. The implementation of these strategic actions is crucial for the achievement of positive results and the desired positioning of Industria Madera Viscarra in the local market.